Pengaruh Entrepreneurial Characteristics, Business Innovation, dan Business Motivation Terhadap Business Success Pada Salon Kecantikan - Muhammad Fauzan Azhmy; Sarah Imelda; Rizky Putri Wardani (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This research aims to determine the influence of entrepreneurial characteristics, business innovation, and business motivation on business success in beauty salons in Medan City. This research uses associative research with a quantitative approach. The population and sample in this research are beauty salons in Medan City with a sample of 86 samples. The data analysis technique uses multiple linear regression analysis with the help of SPSS software. The results of this study show that partially the Entrepreneurial Characteristics, Business Innovation and Business Motivation variables have a positive effect on Business Success. Simultaneously, the variables Entrepreneurial Characteristics, Business Innovation and Business Motivation influence Business.